Why I am a Hindu - Tharoor, Shashi, 1956- (Aleph Book Company, 2018)
"In Why I Am a Hindu, one of India's finest public intellectuals gives us a profound book about one of the world's oldest and greatest religions. Starting with a close examination of his own belief in Hinduism, he ranges far and wide in his study of the faith. He talks about the Great Souls of Hinduism, Adi Shankara, Patanjali, Ramanuja, Swami Vivekananda, Ramakrishna Paramahamsa and many others who made major contributions to the essence of Hinduism"--Amazon.